Estrus Performance and Pregnancy Rate in Types of Local Cows on Different Estrus Synchronization Protocols - Yendraliza, Yendraliza; Lia, Lia; Handoko, Jully; Harahap, Anwar Efendi (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2019)
The research aimed to evaluate the onset of estrus, conception rate, pregnancy rate and duration of estrus in Bali cow, limousine cow and rambon cow after being administered with three different hormones to syncrhronize estrus. A randomized block design with two factors, type of cow and hormone dose, was performed. Fifty-four postpartum cows consisted of the three breeds were administered to a single dose of PGF2Î± (5 ml per cow), a double dose of PGF2Î± (10 ml per cow) and combination of PGF2Î± and hCG (1,500 IU per cow). An analysis of variance showed that different breeds did not associate with the hormone doses and their combination, as evident from the onset of estrus, duration of estrus, conception rates and service per conception. However, different cow breeds showed the same onset of estrus, service per conception and the different onset of estrus and pregnancy rates. On the other hand, different doses of PGF2Î± and its combination with hCG generated different onset of estrus, duration of estrus, and pregnancy rates, but shared common service per conception. In conclusion, Bali cow demonstrated a more appropriate fertility than Limousin cow and Rambon cow. A combination of PGF2Î± and hCG showed the most adequate hormonal treatment to synchronize the estrus compared to single and double doses of PGF2Î±.